Examination of residual stresses in heterogeneous textured materials using diffraction and deformation models - Wroński, Sebastian (My University, 2007)
The aim of this work is to propose a methodology for analysis of mechanical behaviour of polycrystalline materials using diffraction methods and deformation models. A new grazing incidence X-ray diffraction method was developed to study the residual stress gradient. Measurement uncertainties in this technique were studied, especially the influence of: absorption, Lorentz-polarization factor, atomic scattering factor and refractive index. The main purpose is to interpret experimental results on the basis of the elasto-plastic models (self-consistent and Leffers-Wierzbanowski models), which describe the mechanisms of the stress field generation in elasto-plastically deformed polycrystalline materials. Special attention has been paid to the explanation of physical origins of the residual stress, to the prediction of stress evolution and to the influence of residual stress on material properties. Presented models and experimental methods were used for stress analysis in single and multi phase materials. Polycrystalline copper and one and two-phase steels after rolling and cross rolling were investigated. The new method of analysis of multi phase materials was applied. It was used for the estimation of residual stresses and their anisotropy in duplex stainless steel.

Celem pracy było rozwinięcie metodologii pomiaru naprężeń wewnętrznych w materiałach polikrystalicznych przy użyciu metod dyfrakcyjnych oraz modeli deformacji. W pracy rozwinięto nowa metodę pomiaru naprężeń wewnętrznych, przy użyciu stałego kąta padania (grazing incident diffraction method, GID-sin2ψ). Rozpatrzono wszystkie czynniki wpływające na wynik pomiaru takie jak absorpcje, czynnik Lorentza-polaryzacyjny, czynnik atomowy oraz współczynnik załamania oraz zbadano ich wpływ na wyniki pomiaru. Modele deformacji elastoplastycznej (Lefers-Wierzbanowski oraz self-consistent) zostały użyte do interpretacji danych pomiarowych uzyskanych przy pomocy dyfrakcji promieni rentgenowskich oraz promieniowania neutronowego. Dzięki tym modelom możliwe jest przewidywanie naprężeń wewnętrznych generowanych w trakcie deformacji. Specjalną uwagę poświęcono wyjaśnieniu źródła naprężeń oraz ich wpływu na własności mechaniczne materiałów. Zaprezentowane modele oraz metody pomiarowe zostały użyte to badania materiałów jedno- jak i dwufazowych. Badania przeprowadzono dla materiałów: miedźi, stali jedno- i dwufazowej poddanych różnym deformacjom (walcowanie, walcowanie poprzeczne, rozciąganie oraz ściskanie). W pracy zastosowano także nową metodę analizy wyników z doświadczeń (multi-reflection) oraz zastosowano ją do zbadania naprężeń oraz ich anizotropii w stali dwufazowej.
Badanie rozkładu naprężeń wewnętrznych w materiałach polikrystalicznych - metody dyfrakcyjne oraz modelowanie
Diss. École nationale supérieure d'arts et métiers (Paryż), 2007.
Bibliogr.
Keywords: dyfrakcja promieni X; dyfrakcja promieniowania neutronowego; metoda stałego kąta padania; model deformacji; model samouzgodniony; naprężenia wewnętrzne; walcowanie poprzeczne; miedź polikrystaliczna; stal polikrystaliczna; stal dwufazowa; metoda wielorefleksowa; fizyka; inżynieria materiałowa